Doubling rituximab in high‐risk patients with aggressive B‐cell lymphoma ‐results of the DENSE‐R‐MegaCHOEP trial. (5th December 2018) - Friedrichs, Birte; Nickelsen, Maike; Ziepert, Marita; Altmann, Bettina; Haenel, Mathias; Viardot, Andreas; Schmidt, Christian; Ruebe, Christian; Loeffler, Markus; Pfreundschuh, Michael; Rosenwald, Andreas; Glass, Bertram; et al.
Summary: To further improve outcome in young high‐risk patients with diffuse large B‐cell lymphoma (DLBCL) the number of rituximab (R) infusions was doubled in combination with standard CHOEP (cyclophosphamide, doxorubicin, etoposide, vincristine, prednisone) chemotherapy. Seventy‐seven patients (aged 18–60 years) with an age‐adjusted International Prognostic Index of 2–3 received 12 × R (375 mg/m 2 ) on days 0, 1, 4, 8, 15, 22, 29, 43, 57, 71, 85 and 99 together with eight cycles of CHOEP‐14. Results were retrospectively compared to those of patients receiving 6 × R and 8 × CHOEP‐14 in the standard arm of the randomized R‐MegaCHOEP trial. Two‐year overall survival (OS) was 82% [95% confidence interval (CI) 73%–92%]; 2‐year event‐free (EFS) and progression‐free survival (PFS) was 69% (95% CI 59–80%) and 76% (95% CI 66%‐–6%), respectively. Comparing 12 to six doses of R revealed no differences (univariate/multivariate) in EFS (at 2 years: 69% vs. 71%), PFS (76% vs. 75%) and OS (82% vs. 85%), with P  =   0·766, P  =   0·871 and P  =   0·843, respectively. Doubling the number of R infusions concomitant to CHOEP did not improve treatment outcomes. Nonetheless, OS and PFS of young high‐risk patients who received only six infusions of R combined with CHOEP remain excellent and were confirmed in an independent cohort of patients.